If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) + 5(2x + 1) = 27 Reorder the terms: 3(2 + x) + 5(2x + 1) = 27 (2 * 3 + x * 3) + 5(2x + 1) = 27 (6 + 3x) + 5(2x + 1) = 27 Reorder the terms: 6 + 3x + 5(1 + 2x) = 27 6 + 3x + (1 * 5 + 2x * 5) = 27 6 + 3x + (5 + 10x) = 27 Reorder the terms: 6 + 5 + 3x + 10x = 27 Combine like terms: 6 + 5 = 11 11 + 3x + 10x = 27 Combine like terms: 3x + 10x = 13x 11 + 13x = 27 Solving 11 + 13x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 13x = 27 + -11 Combine like terms: 11 + -11 = 0 0 + 13x = 27 + -11 13x = 27 + -11 Combine like terms: 27 + -11 = 16 13x = 16 Divide each side by '13'. x = 1.230769231 Simplifying x = 1.230769231
| -x+6=-27 | | -10=17+x | | 3lox=3.3 | | 177=-y+65 | | -2x+5=-1x+1 | | 3logx=3.3 | | -1x+1=-12 | | 9/x=63/77 | | 5u+3=33 | | 19x+5y=7 | | 17p^2+16=2151 | | f(x)=x^3-1.5x^2-1 | | N/400=2/100 | | 13p^3-3=4209 | | x^(5/3)=1.10 | | 9(11-k)=3(3k-6) | | 4x^2-x+29=0 | | 4x-2=-4-12x | | 4x-2=-4-12 | | 16pqr^2/2pq^2r | | 6(x-2)/5-3(x+1)/5=2(x-5) | | -3cos(2x)-7cos(X)-5=-7 | | 27x^2-25=0 | | (6x)/(4x) | | Y-10+y=22 | | 6c+5d+3c-2d= | | log(x)/4=-1/2 | | 2x-2=x-7 | | lg(x)/4=-1/2 | | 3(x+12)=24-5x | | 2x+17=x+17 | | Y=120-0.25x |